2011
DOI: 10.1021/bm2005214
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure and Phosphorylation of Dentin Matrix Protein 1 (DMP1) and Dentin Phosphophoryn (DPP) Uniquely Determine Their Role in Biomineralization.

Abstract: SIBLING (Small Integrin-Binding Ligand N-linked Glycoproteins) family is the major group of noncollagenous proteins in bone and dentin. These extremely acidic and highly phosphorylated extracellular proteins play critical roles in the formation of collagenous mineralized tissues. While the lack of individual SIBLINGs causes significant mineralization defects in vivo, none of them led to a complete cessation of mineralization suggesting that these proteins have overlapping functions. To assess whether different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 59 publications
7
87
0
3
Order By: Relevance
“…The low levels of DMP1 in the OD-21 cells at this period are corroborated by other investigations (10), demonstrating that DMP1 gene was not detected at day 7, appeared at day 14 and increased at day 21. These data suggest that its expression occurs at later stages, playing a role in biomineralization, regulation of phosphate homeostasis and cell differentiation (22). OSTERIX had its expression higher in OD-21 and MDPC-23 cell groups when compared with OD-21 + OM, indicating that chemical stimuli used in our experiments did not favor the expression of this gene, which has been shown to be expressed in differentiated odontoblasts and to be associated with cell differentiation and tooth-related gene expression at the later stages of tooth development via a RUNX2-independent signaling pathway (23).…”
Section: Discussionmentioning
confidence: 75%
“…The low levels of DMP1 in the OD-21 cells at this period are corroborated by other investigations (10), demonstrating that DMP1 gene was not detected at day 7, appeared at day 14 and increased at day 21. These data suggest that its expression occurs at later stages, playing a role in biomineralization, regulation of phosphate homeostasis and cell differentiation (22). OSTERIX had its expression higher in OD-21 and MDPC-23 cell groups when compared with OD-21 + OM, indicating that chemical stimuli used in our experiments did not favor the expression of this gene, which has been shown to be expressed in differentiated odontoblasts and to be associated with cell differentiation and tooth-related gene expression at the later stages of tooth development via a RUNX2-independent signaling pathway (23).…”
Section: Discussionmentioning
confidence: 75%
“…1 a, 2 a), even when the employed AS solution has no phosphorous in its composition. It seems that phosphorylated extracellular proteins play critical roles in the formation of collagenous mineralized tissues and in the regulation of biomineralization [Deshpande et al, 2011]. However, it has been shown that phosphoproteins are non-specific and may be substituted by other immobilized, naturally occurring phosphoproteins to induce apatite deposition within collagen [Gu et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] These proteins are acidic and highly phosphorylated, and play crucial roles in the mineralization of bone and other collagenous tissues. [ 22,44,49 ] The non-SIBLING proteins contain osteocalcin (OC, 6 kD), which is one of the richest NCPs in bone and is secreted exclusively by osteoblasts; osteonectin (ON, 40 kD), which can interact with calcium ions. [ 48 ] NCPs exhibit multifunctional roles in bone that are crucial for determining the structural hierarchy and mechanical properties of bone.…”
Section: Ncpsmentioning
confidence: 99%